INTEGRASI ANTARA ASPEK LINGKUNGAN DAN EKONOMI DALAM PENGHITUNGAN PDRB HIJAU PADA SEKTOR KEHUTANAN DI KABUPATEN KARANGASEM PROVINSI BALI - Utama, Made Suyana (Bumi Lestari; Vol 9 No 2 (2009), 2009)
In order to avoid the worst impact of development toward the natural resources and environment, it should be considered the new development paradigm that called as sustainable development. Hence, all the development indicators also should be changed, not used the PDB based on SNA (System of National Account) but used The Green PDB system of calculation, that is measured based on the integrated calculation between environmental and economic (System of Integrated Environmental and Economic Account). This research that was carried out in Karangasem Regency, aims to know the contribution of forestry sector toward The Green PDRB, using depletion factor (conflagration and illegal logging) and the environmental degradation of forest management. The research indicated that the green contribution of forestry sector to PDRB of Karangasem Regency is Rp 54,83 million, Rp 75,86 million, and negative Rp 46,64 million from the year 2004, 2005 and 2006, respectively. The negative value of green contribution in year 2006 indicated that of forestry sector as reported on the Brown PDRB Karangasem Regency is less than nature capital which sacrificed due to forest depletion and degradation.
Keywords: environment; economy; development; sustainable